2016
DOI: 10.4292/wjgpt.v7.i3.416
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on the architecture of the ileocecal junction in rats

Abstract: AIM:To evaluate the structural organization of the elastic and collagen fibers in the region of the ileocecal transition in 30 young and old male Wistar rats. METHODS:Histology, immunohistochemistry (IHC), transmission electron microscopy and scanning electron microscopy were employed in this study. The results demonstrated that there was a demarcation of the ileocecal region between the ileum and the cecum in both groups. RESULTS:The connective tissue fibers had different distribution patterns in the two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…It has been reported that the number of endocrine cells in the duodenum changes during aging [39], whereas data on time-dependent alterations in the jejunum are scarce [27]. However, morphological modifications and impaired function were observed in the ileum or at the ileocecal junction at an advanced age [27,40]. We obtained a T score [1] at 11.9% (Figure 5A, left, middle), a correlation coefficient R 2 Y at 0.986 (p = 0.08) and Q 2 at 0.374 (p = 0.30) for duodenum (Figure 5A, right), and NMR-based metabolomics profiling of duodenal metabolites only revealed a decrease in lysine during aging (Figures 5B and S5A,B), despite a trend toward a reduction in all metabolites.…”
Section: Small Intestine Is Metabolically Inert During Agingmentioning
confidence: 99%
“…It has been reported that the number of endocrine cells in the duodenum changes during aging [39], whereas data on time-dependent alterations in the jejunum are scarce [27]. However, morphological modifications and impaired function were observed in the ileum or at the ileocecal junction at an advanced age [27,40]. We obtained a T score [1] at 11.9% (Figure 5A, left, middle), a correlation coefficient R 2 Y at 0.986 (p = 0.08) and Q 2 at 0.374 (p = 0.30) for duodenum (Figure 5A, right), and NMR-based metabolomics profiling of duodenal metabolites only revealed a decrease in lysine during aging (Figures 5B and S5A,B), despite a trend toward a reduction in all metabolites.…”
Section: Small Intestine Is Metabolically Inert During Agingmentioning
confidence: 99%
“…Of course, there is a concern that pieces of split phytobezoar will show difficulty in passing the ileocecal valve in older patients. A laboratory study by de Brito et al [13] using rats reported that the function of the ileocecal junction appears to change with aging, which is associated with changes in the patterns of distribution of collagen and elastic fibers, resulting in increased tensile strength and firmness, but decreased elasticity. However, in humans, there is no clear evidence that aging is related to ileocecal valve incompetence.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the number of endocrine cells in the duodenum changes during aging [39], whereas data on time-dependent alterations in the jejunum are scarce [27]. However, morphological modifications and impaired function were observed in the ileum or at the ileocecal junction at an advanced age [27,40]. We obtained a T score at 11.9%, a correlation coefficient R 2 Y at 0.986 (p=0.08) and Q 2 at 0.374 (p=0.30) for duodenum (Figure 5A), and NMR-based metabolomics profiling of duodenal metabolites revealed only a decrease in lysine during aging (Figure 5B, S5A-B), despite a trend toward reduction in all metabolites.…”
Section: Small Intestine Is Metabolically Inert During Agingmentioning
confidence: 99%